The impact of recreational activities on species at risk in Canada. (December 2022) - Rosenthal, Julie; Booth, Raven; Carolan, Ned; Clarke, Olivia; Curnew, Joshua; Hammond, Cole; Jenkins, Justin; McGee, Emma; Moody, Benjamin; Roman, Joshaua; Rossi, Kassandra; Schaefer, Kai; et al.
Abstract: Recreational activities are among the most common threats to species at risk. The use of standardized threat assessment tables in assessment reports for 300 Canadian species at risk since 2012 enabled a systematic comparison of threat categories considering both frequency and intensity of threats. Our analysis of these reports reveals that recreational activities are the most common threat to species at risk in Canada, affecting more species than any other threat category. However, the intensity of a threat should be considered. When accounting for the intensity of threats, recreational activities are the third-greatest threat to species at risk in Canada following "Invasive Non-native/Alien Species" and "Roads and Railroads". Recreational activities were among the top five threats to molluscs, vascular plants, mosses, arthropods, marine and terrestrial mammals, and reptiles considering both frequency and intensity of threat to the assessed species in each taxonomic group. Among species at risk for which recreational activities posed at least a low-level threat, off-road vehicle use was the most commonly mentioned recreational threat. The second-most common recreational threat was hiking. Boating, mountain biking, camping, beach use, horseback riding, off-leash pets, and rock climbing were considered at least a low-level threat to five or more species. Common mechanisms of threat arising from recreational activities include direct mortality and damage from trampling species and/or their habitat, siltation and changes to water chemistry, disruption due to human presence, and noise disturbance. Management implications: Recreation activities affected more species at risk than any other category of threat. The intensity of threat from recreational activities was negligible or low for most at-risk species affected. However, increases in recreational use and cumulative effects could result in more severe threats in the future. Both mechanized and non-mechanized recreational activities cause direct mortality, disturbance, and/or degradation of habitat for species at risk in Canada including many under-studied taxa. Thus, recreational activities that are typically unauthorised and those that are commonly permitted in protected areas warrant management attention to avoid impacts on species at risk, especially less conspicuous taxa.